The Effect of Financial Conditions and Disclosure on Going Concern Audit Opinion - Dea Annisa; Tri Utami; Dila Angraini (EAJ (Economic and Accounting Journal), 2022)
The purpose of this study is to determine the effect of financial condition and disclosure on going concern audit opinion. This research is conducted on finance companies listed on the Indonesia Stock Exchange (IDX) in 2015 – 2019. This type of research is quantitative research with sampling using purposive sampling method. The sample used is 70 audited financial statements from 14 companies with an observation period of 5 (five) years. Data analysis techniques used are descriptive statistics, logistic regression analysis and hypothesis testing. The results of the study state that partially the financial condition does not affect the continuity of the audit opinion, and disclosure has an effect on the continuity of the audit opinion. while simultaneously, financial condition and disclosure affect going concern audit opinion.